Genetic Frequency Analysis of Digitalis Finger Segments, Case Study of Students at the UIN Sulthan Thaha Jambi Campus - Annisa, Rahma; Ritonga, Nisma Hariyanti; Marsa, Andina Dwiana; Alinza, Cheryska; Anggrai Ningsih, Nuraisyah Lord (ORGANISMS: JOURNAL OF BIOSCIENCES, 2025)
Rolling tongue (the ability to fold the tongue into a certain shape like a roll) is often used as a topic in genetic research because it is considered an example of simple genetic inheritance. This phenomenon involves a person's ability to roll the tongue up laterally which is often assumed to be a trait determined by a single dominant gene. However, further studies have shown that Rolling tongue is likely influenced by complex genetic and environmental factors. This study aims to determine the population of students at the State Islamic University of Sultan Thaha Saifuddin Jambi who can perform the Rolling tongue movement and also examine the factors that influence a person to be able to perform the Rolling tongue movement . This study uses a quantitative method with an observational approach to observe variations in the Rolling tongue phenotype in UIN STS Jambi students. From this study, it was found that the number of respondents was 104 students who were tested for Rolling tongue ability, who could perform the Rolling tongue movement were more than students who could not perform the movement. By analyzing data from various populations, this study concluded that Rolling tongue is not entirely inherited in a simple dominant manner but involves interactions between genetics and the environment